Optimizing School Community Assets for the MBG Program Through the ABCD Approach Towards Sustainable Community-Based Food Security - Dhuhaa Rohmawan; Muhammad Yasminto; Nur Huda (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: The Free Nutritious Meals (MBG) program in Tertek Village, Pare District, Kediri Regency faces challenges in utilizing local assets for sustainable implementation. Purpose: This community service program aims to optimize school and community assets using the Asset-Based Community Development (ABCD) approach to improve children's nutritional status and establish a sustainable food security model. Methods: The ABCD approach was implemented through five stages: Discover (asset mapping), Dream & Design (participatory planning), Delivery (implementation of food gardens and public kitchen), Evaluate & Sustain (monitoring and reflection). Participants included 85 students, 23 volunteers, and 9 donor parties. Data were collected through pre-post tests, observation, FGDs, and kitchen production logs. Results: Asset mapping identified 1,200 m² of unused land converted into a productive garden, producing 35 kg of vegetables/month. Nutritional literacy improved by 19.3 points (from 62.4 to 81.7; paired t-test, p<0.001). Beneficiaries expanded from 0 to 85 students, volunteers increased from 5 to 23 persons, and active donors from 2 to 9 parties. Food cost efficiency reached 27% savings. Community participation in mutual cooperation increased by 60%. Conclusion: The ABCD approach effectively mobilized fragmented local assets into an integrated food security ecosystem, significantly improving children's nutrition and strengthening community self-reliance. The program provides a replicable model for asset-based nutrition interventions in religious community contexts.